온톨로지 기반의 서비스 상호운용을 위한 협업 시스템 - 황치곤; 문석재; 정계동; 최영근; Hwang, Chi-Gon; Moon, Seok-Jae; Jung, Kye-Dong; Choi, Young-Keun (한국정보통신학회논문지, 2013)
The development of collaboration among information systems in accordance with changes in enterprises' business environment brings about the problems of duplication of the existing business services and increase in costs of maintenance. Accordingly, Web service has been suggested as the standard of distributed computing to prevent the duplication of services within the same business domain and to attain the services that are already being utilized. But since the data needed for Web services are not standardized, it is difficult for the users to find services that meet diverse business purposes. In this paper, we construct an ontology-based collaboration system for service interoperability. The ontology can support fusion service by finding services which are existed interdependently under the distributed environment for collaboration processing. The role of the collaborative system includes development, registration and call of services based on ontology. A local systems request collaboration support through the service profile. Collaborative system supports the development of service using the service profiles, represents the semantic association between real data through system ontology, and infers relationship between instances contained in the services. Based on this, we applied the travel booking services for collaboration system. As a result, service can be managed effectively preventing collision in collaborative system, and we verify that the mapping between system is reduced. 기업의 업무 환경 변화에 따른 정보 시스템 간의 협업 개발은 기존 업무 서비스의 중복 및 유지보수 비용의 증가라는 문제가 발생한다. 이에 따라 웹 서비스는 동일한 비즈니스 도메인 내 서비스의 중복을 방지하고 이미 활용 중인 서비스를 위한 분산 컴퓨팅의 표준으로 제안되었으나, 웹 서비스가 필요로 하는 데이터가 규격화되어 있지 않기 때문에 사용자는 다양한 비즈니스 목적에 부합하는 서비스를 찾기 어렵다. 따라서 본 논문에서는 서비스 운용을 위한 온톨로지를 기반으로 한 협업 시스템을 구축한다. 온톨로지는 협업 처리를 위한 분산 시스템 환경 하에서 상호 의존적으로 존재하는 서비스를 찾아 융합 서비스를 지원할 수 있다. 협업 시스템의 역할은 온톨로지를 기반으로 서비스의 개발, 등록 및 호출하는데 사용 한다. 로컬 시스템은 서비스 프로파일을 통해 협업 지원을 요청한다. 협업 시스템은 해당 서비스 프로파일을 참조하여 개발을 지원하고, 온톨로지를 통해 실 데이터 간의 의미적 연관관계를 표현하며, 서비스에 포함된 인스턴스들에 대한 관계를 추론한다. 이를 바탕으로 여행 예약 서비스를 위한 협업 시스템에 적용한다. 그 결과로 협업 시스템에서 발생하는 데이터 충돌 문제를 해결하여 서비스를 효율적으로 관리할 수 있으며, 시스템 간의 매핑이 감소됨을 검증한다.